PENGEMBANGAN TES BAKAT PENCAK SILAT - Rony Syaifullah (PJKR FKOR UNS, 2019)
category which includes Anthropometic, Physiological, Biomotor and Technical. This research refers to the developmental research conveyed by Borg and Gall. From the instrument process, then it trials and applys into a small and a big sample. The result of experiment was made as the base of making Software which can be made as a model in conducting a test of talent identification especially on sport branch of Pencak Silat for age of 12-14. In the Model of this Test, there are 15 series of test consisting of Anthropometric of 4 test forms, Physiological of 3 test forms, Biomotor of 4 test forms and Tehnic 4 test forms. The results from 15 items of the test are then put in the software, a reference in the form of recommendation that the athlete candidate Has Talent of Pencak Silat, Has Enough Talent of Pencak Silat and Has Less Talent of Pencak Silat is obtained.After obtaining the validity and the reliability of the test instrument and obtaining the norm of all test instruments and the weight of each test instrument, a software of talent test of pencak silat named “RS Silat Tallent Test”. It could be concluded that the result of this research was the arrangement of a model of tallent test especially for the sport branch of Pencak Silat for the athletes of the age of 12 up to 14 had been conducted named “RS Silat Tallent Test”.